Analisis Stres Kerja di Masa Pandemi Covid-19 pada Karyawan Mina Wisata Islami Tour and Travel Haji Umrah Surabaya - Aisyah Puteri Arini; Airlangga Bramayudha (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2022)
The purpose of this research is to describe the causal factors, countermeasures, and obstacles in overcoming work stress during the Covid-19 pandemic in Employees of Mina Wisata Islami Tour And Travel Haji Umrah Surabaya. This research uses qualitative research methods with case studies as a type of research. Case studies are used to observe, describe, and find a complete picture of the phenomenon related to work stress during the Covid-19 pandemic in employees of Mina Wisata Islami Tour and Travel Haji Umrah, Surabaya. The data collection technique used to dig up information from Mina Wisata Islami Tour and Travel Haji Umrah Surabaya is through interviews, observations and documentation. As a result of research obtained by researchers in the field illustrates that the factors that cause work stress in Mina Wisata Islami employees are dominated by changes in conditions and unclear information simultaneously, so employees have no power over it. As for some other stressors that can trigger the onset of work stress for employees, namely work demands, time demands, dual roles, feedback that is felt less after when carrying out work, work environment conditions, and unhuffed authority to carry out responsibilities. Related to efforts to combat employee work stress using three methods, namely social support, self-soothing, and self-evaluation. Related obstacles in stress management efforts lie in work ineffectiveness, time inefficiencies, information vagueness, and individual characteristics.